Characterization of immune responses to virulent African swine fever virus in domestic pigs - Madden, Daniel (My University, 2026)
African swine fever (ASF) has remained a perennial threat to global pork production in large part due to the lack of a widely available efficacious vaccine. The disease, caused by African swine fever virus (ASFV), is devastating to pig farmers and associated with very high pig mortality and significant economic losses. Progress toward ASFV vaccine development has been hindered by the complex biology of the virus and an incomplete understanding of the mechanisms which govern protective immunity to ASFV. ASFV strains possess considerable genetic diversity, and the biological functions of many ASFV proteins and their potential contributions to viral virulence are unknown. While it is known that protective immunity to ASFV can be induced, the differences between protective, non-protective and pathological immune responses to ASFV are unclear. The lack of a comprehensive understanding of these topics is a major challenge for rational vaccine design for this disease. To better characterize the immune responses which are mounted in response to virulent ASFV, we performed three in vivo infection experiments in domestic pigs. For the first study, pigs were lethally infected with the Armenia 2007 genotype II ASFV isolate, and innate and adaptive post-infection immune responses were assessed throughout the course of the disease through multiple techniques including plasma cytokine quantification, flow cytometry, and transcriptomic profiling of blood cells. The manifestation of clinical disease coincided with the appearance of significant elevations in multiple plasma cytokines, and late disease was characterized by elevated proinflammatory cytokine levels, enrichment of genes related to innate immunity and antiviral immune responses, depletion of circulating B cells, and an abrupt increase in CD203a+ circulating macrophages prior to death. In the second study, we assessed whether pigs lacking CD1d, an MHC class I-like protein which was shown to facilitate receptor- mediated uptake of ASFV in vitro, were refractory to infection with the highly virulent genotype II ASFV strain MNG19. CD1D knockout piglets created using a CRISPR-Cas9 system showed no resistance to ASFV infection and developed fatal disease highly similar to that observed in age-matched wildtype control animals. In the third study, we evaluated the role of the viral polymerase X (PolX) protein in the virulence of the ASFV isolate Armenia 2007, with the overall aim of creating an attenuated virus for use as a modified live virus (MLV) vaccine. We were able to demonstrate that PolX alone is not essential for ASFV virulence, and the lack of PolX does not promote the accumulation of mutations in the viral genome during replication in vivo. Taken together, this research provides new insight into: (i) details regarding the specific host responses which manifest during fatal ASF in domestic pigs; (ii) the significance of pig CD1d for ASFV replication and virulence in vivo; and (iii) the function of the ASFV protein PolX in the replication cycle of ASFV. This knowledge can be used to advance the fields of ASFV immunology and rational vaccine development for this devastating disease.
Keywords: African swine fever; African swine fever virus; Immunology; Innate immunity; Viral immunology